2016
DOI: 10.1111/jce.13017
|View full text |Cite
|
Sign up to set email alerts
|

Acute Autonomic Engagement Assessed by Heart Rate Dynamics During Vagus Nerve Stimulation in Patients With Heart Failure in the ANTHEM‐HF Trial

Abstract: Acute Heart Rate Dynamics During VNS. Background: Chronic vagus nerve stimulation (VNS) applied to produce biomimetic levels of parasympathetic activation is feasible, well tolerated, safe, improves left ventricular ejection fraction, NYHA class, heart rate variability, and baroreflex function, and reduces T-wave alternans (TWA) in patients with chronic heart failure. However, the acute effects of VNS on beat-to-beat heart rate dynamics have not been systematically characterized in humans. Methods and Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 28 publications
1
24
0
Order By: Relevance
“…After animals recovered from the vagus nerve implant surgery, proper function of the cuff electrode was validated by measuring changes in heart rate and pupil size following VNS. Both heart rate reduction (Nearing et al, 2016) and pupil dilation (Desbeaumes Jodoin et al, 2015; Bianca and Komisaruk, 2007) in response to VNS have been reported previously. We measured pupil size fluctuations over time with and without 1 sec stimulation of the vagus nerve.…”
Section: Resultssupporting
confidence: 66%
“…After animals recovered from the vagus nerve implant surgery, proper function of the cuff electrode was validated by measuring changes in heart rate and pupil size following VNS. Both heart rate reduction (Nearing et al, 2016) and pupil dilation (Desbeaumes Jodoin et al, 2015; Bianca and Komisaruk, 2007) in response to VNS have been reported previously. We measured pupil size fluctuations over time with and without 1 sec stimulation of the vagus nerve.…”
Section: Resultssupporting
confidence: 66%
“…Function of the cuff electrode was validated by measuring changes in heart rate ( Nearing et al, 2016 ; see Materials and Methods) and pupil size following VNS ( Bianca and Komisaruk, 2007 ; Desbeaumes Jodoin et al, 2015 ; Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ANTHEM-HF trial used VNS in 59 heart failure patients, and found that VNS caused subtle changes in heart rate when applied on both the right and left side of the body. They concluded that the use of VNS in human subjects is a viable option for the modulation of the effects of the ANS on the heart (Nearing et al 2016). Another large-scale trial is the INOVATE-HF trial, in which 707 patients were followed over several months.…”
Section: Heart Failurementioning
confidence: 99%